21) \( \frac{4^{2 x-1}}{4^{2 x}}=4^{3 x} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the equation \( \frac{4^{2x-1}}{4^{2x}}=4^{3x} \), we can simplify the left side using the property of exponents: \[ \frac{4^{2x-1}}{4^{2x}} = 4^{(2x-1)-2x} = 4^{-1} = \frac{1}{4} \] Now the equation can be rewritten as: \[ \frac{1}{4} = 4^{3x} \] Since \( 4 = 4^1 \), we can express \( \frac{1}{4} \) as \( 4^{-1} \): \[ 4^{-1} = 4^{3x} \] Now we can set the exponents equal to each other because the bases are the same: \[ -1 = 3x \] Solving for \( x \) gives: \[ x = -\frac{1}{3} \] The solution to the equation is \( x = -\frac{1}{3} \).